Imagining religious toleration a literary history of an idea, 1600-1830 - Conway, Alison; Alvarez, David 1966- (University of Toronto Press, 2019)
Formerly a site of study reserved for intellectual historians and political philosophers, scholarship on religious toleration, from the perspective of literary scholars, is fairly limited. Largely ignored and understudied techniques employed by writers to influence cultural understandings of tolerance are rich for exploration. In investigating the eighteenth-century novel, Alison Conway, David Alvarez, and their contributors shed light on what literature can say about toleration, and how it can produce and manage feelings of tolerance and intolerance. Beginning with an overview of the historical debates surrounding the terms "toleration" and "tolerance," this book moves on to discuss the specific contributions that literature and literary modes have made to cultural history, studying the literary techniques that philosophers, theologians, and political theorists used to frame the questions central to the idea and practice of religious toleration. Tracing the rhetoric employed by a wide range of authors, the contributors delve into topics such as conversion as an instrument of power in Shakespeare; the relationship between religious toleration and the rise of Enlightenment satire; and the ways in which writing can act as a call for tolerance